Work‐function‐induced Interfacial Built‐in Electric Fields in Os‐OsSe2 Heterostructures for Active Acidic and Alkaline Hydrogen Evolution. (28th July 2022) - Chen, Ding; Lu, Ruihu; Yu, Ruohan; Dai, Yuhang; Zhao, Hongyu; Wu, Dulan; Wang, Pengyan; Zhu, Jiawei; Pu, Zonghua; Chen, Lei; Yu, Jun; Mu, Shichun
Abstract: Theoretical calculations unveil that the formation of Os‐OsSe2 heterostructures with neutralized work function (WF) perfectly balances the electronic state between strong (Os) and weak (OsSe2 ) adsorbents and bidirectionally optimizes the hydrogen evolution reaction (HER) activity of Os sites, significantly reducing thermodynamic energy barrier and accelerating kinetics process. Then, heterostructural Os‐OsSe2 is constructed for the first time by a molten salt method and confirmed by in‐depth structural characterization. Impressively, due to highly active sites endowed by the charge balance effect, Os‐OsSe2 exhibits ultra‐low overpotentials for HER in both acidic (26 mV @ 10 mA cm −2 ) and alkaline (23 mV @ 10 mA cm −2 ) media, surpassing commercial Pt catalysts. Moreover, the solar‐to‐hydrogen device assembled with Os‐OsSe2 further highlights its potential application prospects. Profoundly, this special heterostructure provides a new model for rational selection of heterocomponents. Abstract : A bidirectional favorable charge balance is generated at Os‐OsSe2 interfaces. The built‐in electric field provides highly efficient HER active sites, accelerating the kinetics toward water electrolysis for hydrogen production.